Smallholder Livelihood Risks and Barriers to Adoption of Drought Tolerant Maize Varieties in Uganda - Nakanwagi, Josephine (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
Maize is an important crop grown in most parts of the Uganda for food, feed and income, (Asea. et al, 2014). Given climate risk to agricultural seasons, drought tolerant maize varieties can play an important role in maintaining production and protecting livelihoods. Potential barriers for uptake of advanced seed technology could be that farmers lack information to assess benefits of drought tolerant maize, or because of liquidity constraints, or downside risk. Recent empirical literature argues that downside risk, for example risk of substantial income loss associated with weather shocks, may deter farmers to invest in production enhancing technology such a certified seed (Emerick et al., 2016). This despite the fact that the seed has a much higher yield potential and is often more drought tolerant than the varieties traditionally grown by farmers (CCAFS, 2019). Farmers rely mostly on home-saved seed and low quality products from local markets. Agricultural production outputs cannot be predicted with certainty, unlike most nonagricultural enterprises due to external factors such as weather, pests, and diseases (Kansiime and Mastenbroek, 2016). Rainfall variability influenced by large scale inter-seasonal and interannual variability resulting in frequent extreme weather events is among the major risk factors affecting agricultural production and food security in Uganda. With only 0.1% of land irrigated, changes in rainfall greatly impact the rain-fed agricultural sector as well as the ability to achieve broader development objectives in Uganda (James, 2010). The increased uncertainty of climate effects represents an additional problem to farmers that translates into production risks associated with crop yields. However, the risk spectrum faced by farmers involves various climate and macro-economic factors, as well as seed and farming choices, facing a time span from planting until harvest, storage and marketing and could be different for male and female farmers. The Integrated Seed Sector Development (ISSD) under Wageningen UR Uganda Limited in collaboration with Wageningen University, Development Economics Group, The Netherlands, International Research Institute for Climate and Society (IRI) at Columbia University, United States and The CGIAR Research Program on Climate Change, Agriculture and Food Security (CCAFS) have implemented research on Male and female livelihood risks and barriers to adoption of drought tolerant maize varieties under a project entitled: Promoting Climate Resilient Maize Varieties in Uganda (PROMO) To enhance the understanding of why farmers are not buying quality seed, but mainly use home-saved seed and re-plant grain from the local market, Promoting Climate Resilient Maize Varieties in Uganda (PROMO) project conducted a research study on male and female farmers’ perceived risks spectrum, economic barriers to adoption and low willingness to pay for hybrid drought tolerant maize seed and other agricultural inputs. The research team under ISSD Uganda organized an online webinar with the major objective of sharing key findings of the research study with different stakeholders along the maize value chain.